Strategi Komunikasi Persuasif Admin Online Untuk Menarik Minat Pembeli Di Toko Online Samudracomp - Rohmah, Suci Nur; Prihandoyo, Windi Baskoro; Suryani, Nining (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2024)
This research aimed to find out the strategy of persuasive communication which implemented by online admin in effort to attract buyers' interest at Samudracomp online store. The method used is a descriptive qualitative with data collection techniques formby structured interview, observation and documentation. The research results show that the persuasive communication strategy which implemented by online admin in services can influence buyers' interest in Samudracomp, the number of visitors to Samudracomp online store in 2023 was only 210 followers, after the increase in online admin services the amount of followers increase to 322 in 2024, positive reviews given by buyers and the increase in number of products that sold in Samudracomp online store.